1976
DOI: 10.1113/jphysiol.1976.sp011380
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of the heparin‐neutralizing factor in blood platelets.

Abstract: SUMMARY1. The distribution of the heparin-neutralizing factor (platelet factor 4, PF4) in subcellular organelles of blood platelets of rabbits and man was investigated.2. In both species the organelles storing 5-hydroxytryptamine (5-HT storage organelles) contained only trivial amounts of PF4.3. In contrast, the content of PF4 was highest in the subcellular fractions rich in a-granules.4. In conclusion, PF4 is probably localized in the a-granules and there.-fore the platelets contain at least two types of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…It has been suggested that antiheparin activity is located in the alpha granules of platelets (19,20). Holmsen et al (21) have reported that higher concentrations of thrombin are needed for alpha granule release than for dense body secretion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that antiheparin activity is located in the alpha granules of platelets (19,20). Holmsen et al (21) have reported that higher concentrations of thrombin are needed for alpha granule release than for dense body secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent observations indicate that the interaction of platelets with clotting factors during thrombin formation is more complex than initially postulated. Osterud et al (2) have shown that platelets contain an activated form of Factor V and have postulated Received for publication 19 December 1977 and in revised form 23 january 1978. that its release may be important in prothrombin activation. Experiments by Miletich et al (3) demonstrate that the rate of thrombin generation is 10 to 100-fold faster when platelets are used in place of phospholipid and Factor V in the activation of prothrombin by Factor Xa.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for isolation of human e-granules have been reported in the past [8,11] but the fact that improvements on these methods are still being introduced [19] is an indication that they are only partially satisfactory. In this report, pig e-granules prepared by a modification of pre-existing procedures [8,16,40] were analyzed biochemically and morphologically.…”
Section: Discussionmentioning
confidence: 99%
“…The latter include platelet factor 4, fl-thromboglobulin, a cell growth factor, fibronectin, factor V, thrombospondin, 0%-antiplasmin and fibrinogen. Each group of exported molecules is thought to be stored in a distinct secretory organelle: serotonin, Ca + + and the adenine nucleotides are localized in the dense granules [12,13,16]; hydrolases are thought to be stored in lysosomes [5,11] and the polypeptide macromolecules are found in a third type of organelle, the 0~-granule [11,27,28,48,49]. Studies on patients with the "gray platelet" syndrome and with storage pool disease have shed some light on the compartmentation of the released products.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the possibility that proelastase and its trypsin-like acti vator be localized in different light granules should not be discarded and is supported by the possible existence in platelets of different types of a-granules as suggested by Morgenstern et al [27] and Salganicoff et al [31]: these last authors have clearly demonstrated the wide distribution of lyso somal enzymatic markers in various subfractions separated in particular conditions from a platelet homogenate. A heterogeneity of the dense bodies has also been shown by Da Prada et al [8] since platelet factor IV is located in granules distinct from the serotonin and adenine nucleotides storage granules. Whatever the precise localization of proelastase and its activator be, an important point has been raised by Nachman and H arpel [28] who have recently shown the presence of a 2-macroglobulin and oq-antitrypsin in fractions obtained from solubilized platelet membranes and granules: the trypsin-like enzyme could thus be inhibited in an enzyme-inhibitor complex which could be directly or indirectly dissociated after adhesion of the platelet to collagen.…”
Section: Discussionmentioning
confidence: 70%